Pendampingan Persiapan Tes TOEFL bagi Bintara Mahasiswa Politeknik Angkatan Darat (POLTEKAD) - Degeng, Putu; Unsiah, Frida; Iswahyuni, Iswahyuni; Isnaini, Muhammad; Widiyati, Theresia (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
ABSTRACT Mentorship program is one of recommended ways that can be used to assist the SDGs, particularly Quality Education. The goal of this program is to prepare students to take the English Language Proficiency Test (TOEFL), as one of graduation requirements. Since not all students have access to TOEFL preparation, this assistance is crucial to help them overcome the obstacles they confront before taking the test. Attaining the targeted TOEFL score becomes difficult when there are constraints on time, resources, and study tools. Fifty-five students in grade IV in one of vocational schools called as Bamasis in East Java Indonesia participated in the support. TOEFL tests as trial tests were conducted before and after the mentorship to find out the students’ scores and compare their scores. In addition, questionnaire distribution was conducted to find out Bamasis’ perception of the mentorship. The findings show that the students’ scores have improved greatly before and after the mentorship. Students give positive responses regarding the implementation of mentorship in terms of the mentor performance, TOEFL material appropriateness and clarity, and students’ facilities. It implies that mentorship is beneficial for the students since they give students opportunities to drill themselves and get them familiar with TOEFL test items.